Fronts of the Malvinas Current System: Surface and Subsurface Expressions Revealed by Satellite Altimetry, Argo Floats, and Mercator Operational Model Outputs - Artana, Camila Indira (2018)
We examine the surface and subsurface signature of ocean fronts closely associated with the Malvinas Current dynamics. We first evaluate the performances of the Mercator Ocean eddy permitting (1/12° spatial resolution) global operational system in the southwestern Atlantic Ocean over the last 10 years (2007–2016) using satellite, Argo float and in situ data collected near 41°S. Observations versus model comparisons show that the model correctly reproduces the general circulation and the complex hydrographic features of the study area including the vicinity of the Brazil-Malvinas Confluence. The model outputs accurately match the observations except in June 2015. The causes for the June 2015 mismatch are analyzed. We then used the model and satellite altimetry to identify isolines of absolute dynamic topography (ADT) and potential density at different depths associated with the mean front location and establish their correspondence with specific water mass boundaries. Frontal displacements as depicted in satellite ADT, model ADT, and model potential density at 450 m are in general agreement. The ADT and potential density at 450 m provide nonidentical and complementary information on eddies shed by the Polar Front (PF): while ADT depicts the surface circulation with PF eddies entrained into the energetic circulation over the deep Argentine Basin, potential density at 450 m is more effective at monitoring PF eddies feeding the Malvinas Current.